Determining diagnostic indicators for neuropathic pain in patients with osteoarthritis - Bashir, Farhat (Curtin University, 2021)
This research aimed to differentiate neuropathic and inflammatory pain among osteoarthritis participants. Osteoarthritis participants were evaluated using self-report pain and function questionnaires, sensory and pain measures, proprioceptive function, MRI and biomarkers. Results indicated osteoarthritis participants had significant sensory deficit. 48% of participants were categorised as having neuropathic pain. A number of key measures were identified that can assist in diagnosing neuropathic pain. This information will be helpful in more effectively managing pain in osteoarthritis.